14-3-3 proteins—a moonlight protein complex with therapeutic potential in neurological disorder: in-depth review with Alzheimer’s disease - Abdi, Gholamareza; Jain, Mukul; Patil, Nil; Upadhyay, Bindiya; Vyas, Nigam; Dwivedi, Manish; Kaushal, Radhey Shyam (Frontiers in Molecular Biosciences, 2024)
Alzheimer’s disease (AD) affects millions of people worldwide and is a gradually worsening neurodegenerative condition. The accumulation of abnormal proteins, such as tau and beta-amyloid, in the brain is a hallmark of AD pathology. 14-3-3 proteins have been implicated in AD pathology in several ways. One proposed mechanism is that 14-3-3 proteins interact with tau protein and modulate its phosphorylation, aggregation, and toxicity. Tau is a protein associated with microtubules, playing a role in maintaining the structural integrity of neuronal cytoskeleton. However, in the context of Alzheimer’s disease (AD), an abnormal increase in its phosphorylation occurs. This leads to the aggregation of tau into neurofibrillary tangles, which is a distinctive feature of this condition. Studies have shown that 14-3-3 proteins can bind to phosphorylated tau and regulate its function and stability. In addition, 14-3-3 proteins have been shown to interact with beta-amyloid (Aβ), the primary component of amyloid plaques in AD. 14-3-3 proteins can regulate the clearance of Aβ through the lysosomal degradation pathway by interacting with the lysosomal membrane protein LAMP2A. Dysfunction of lysosomal degradation pathway is thought to contribute to the accumulation of Aβ in the brain and the progression of AD. Furthermore, 14-3-3 proteins have been found to be downregulated in the brains of AD patients, suggesting that their dysregulation may contribute to AD pathology. For example, decreased levels of 14-3-3 proteins in cerebrospinal fluid have been suggested as a biomarker for AD. Overall, these findings suggest that 14-3-3 proteins may play an important role in AD pathology and may represent a potential therapeutic target for the disease. However, further research is needed to fully understand the mechanisms underlying the involvement of 14-3-3 proteins in AD and to explore their potential as a therapeutic target.